Empirical Observations on LoRa Performance for Different Environments - Dogan, Gurkan; Yildirim, Gungor; Tatar, Yetkin (Ieee, 2019)
LoRa (Long Range) is a patented modulation scheme based on the chirp spread-spectrum (CSS) technique. This technique is implemented in the physical layer of LoRaWAN, which is one of today's prominent low power area (LPWA) technologies. The most important feature of LoRa is that it can enable long-range communication as well as a low data rate and low energy consumption. This study focusses on LoRa's performance in different environments. Although naturally its outdoor performance is heeded more, this study also observes LoRa's indoor performance. Outdoor test locations are urban areas, recreation areas with trees and high hills with a good Fresnel Field. Indoor measurements have been carried out in two environments. The first one is a building with multi-floor. The second one is a tunnel environment with a narrow-section. For each test environment, the packet delivery ratio (PDR), RSSI and SNR values are observed. Finally, the observed results are discussed.
3rd International Conference on Applied Automation and Industrial Diagnostics (ICAAID) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: LoRa; LoRaWAN; tunnel; indoor; outdoor